OPN Gene Polymorphism and the Serum OPN Levels Confer the Susceptibility and Prognosis of Ischemic Stroke in Chinese Patients - Meng Jing; Baoxin Li; Xuwei Hou; Jayaram Shoba; Changyu Li; Hongsheng Liang; Xiangtong Zhang; Enzhong Liu; Baofeng Yang; Xiangxi Meng (Cellular Physiology and Biochemistry, 2013)
Aim: To investigate the association of Osteopontin (OPN) gene polymorphism and serum thrombin-cleaved OPN level with the susceptibility to ischemic stroke (IS) and its prognosis. Methods: A total of 377 patients with IS and 551 healthy individuals were recruited. The OPN gene polymorphisms at -156 G>GG, -443 C>T and -66 T>G were genotyped. Serum full-length and the thrombin-cleaved OPN were determined. Results: We found that only the -443 C>T polymorphism was significantly associated with the susceptibility to IS. The -443 CC represented a near 2 time higher risk for IS incidence than TT carriers. Also, the -443 CC genotype had significantly poorer outcome and they significantly had higher occurrence for bad recovery as determined by modified Rankin Scale (mRS) (OR=2.18, p=0.043) and Barthel Index (BI) (OR=2.12, p=0.05). The mean serum thrombin-cleaved OPN level in IS group were significantly higher than that in control group. ROC analysis showed that the thrombin-cleaved OPN level (cut-off value, 166.8 ng/ml) can discriminate IS patients from controls with a specificity of 86.3% and a sensitivity of 57.7%. The serum thrombin-cleaved OPN was significantly associated with the clinical outcome at 12 months after discharge from hospital. Conclusion: These results suggest that the -443 C>T polymorphism of OPN gene and serum thrombin-cleaved OPN can be used as a biomarker for the susceptibility and prognosis of IS patients.